Development of aerobic granules using Sequencing Batch Reactor (SBR): a proposed workflow / Azlina Mat Saad ... [et al.] - Mat Saad, Azlina; Dahalan, Farrah Aini; Ibrahim, Naimah; Yusuf, Sara Yasina (2017)
This study highlights on the development of aerobic granules using sequencing batch reactor (SBR). The development involves four phases; fill, aerate, settle, and draw in every cycle. In easing the understanding; the flowchart, schematic diagram, and list of equipment are presented in this paper. Sampling is another important stage in completing the process. In addition, the composition of synthetic wastewater including nutrients and trace elements are detailed out in this paper. In monitoring the development of aerobic granules, several parameters should be measured consistently. As a guideline, expected results have been listed in ensuring the smoothness of the proposed workflow.